Being With Objects of Meaning: Cherished Possessions and Opportunities to Maintain Aging in Place. (17th November 2018) - Coleman, Tara; Wiles, Janine
Abstract: Background and Objectives: Research regarding the role that cherished possessions play in experiences of aging and daily life has tended to focus on how possessions assist individuals in "looking back" and remembering important experiences, relationships, and identities. Here, we consider how the possessions that older adults keep at home inform their present experiences of aging and also facilitate the ongoing maintenance of aging in place. Research Design and Methods: We employed an interpretive phenomenologically inspired research strategy that enabled an in-depth examination of older adult's experiences of cherished possessions. This approach emphasized participants' own situated meanings. In-depth interviews were followed by participatory photo-elicitation interviews and journaling. Results: The majority of study participants interacted with cherished possessions to connect with their past selves, but also to cope with times of challenge and change in the present, and in some cases, to cultivate a sense of being able to maintain aging in place. For some older adults, however, possessions disrupted sense of self, place attachment, and daily life. Cherished possessions, therefore, play a significant role in opportunities to maintain aging in place. Discussion and Implications: The material culture of home and its relationship to experiences of aging may provide or disrupt opportunities to maintain aging in place. Interventions based on possessions that are easy to access and employ to provide comfort and affirm peoples' preferred relationships to self, others, and the living environment could make a difference to the quality of life for older adults.